DETERMINANT SUCCESS FACTORS IN IMPLEMENTATING MB-KM AND ITS IMPACT ON STRENGTHENING THE CAPACITY OF GRADUATES - Ismawati, Linna; Riyanto, Agus; Budiarti, Isniar; Santy, Raeni Dwi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
The aim of this study was to examine the determinants of the success of MB-KM implementation and their impact on strengthening the capacity of graduates in the Program Studi Manajemen FEB UNIKOM. The method used in this research is descriptive qualitative using SWOT analysis. Samples were taken randomly consisting of lecturers, education staff, and active students in the Management Study Program FEB UNIKOM through questionnaires, observation and documentation. The results show that the factors that determine the success of MB-KM implementation and its impact on influencing the quality of graduates consist of the readiness of human resources, curriculum development that adapts to the industrial revolution 4.0, facilities, infrastructure and information technology, as well as support from the entire academic community, and work. same partnership. In order to achieve this, the right strategy to be taken by the Program Studi Manajemen FEB UNIKOM is a horizontal integration strategy with an emphasis on internal and external MB-KM cooperation and partnerships. This is because cooperation and strategic partnerships provide indispensable support for the success of the MB-KM program in the Program Studi Manajemen FEB UNIKOM. With this program, it can be used as a reference and evaluation in the implementation of the MB-KM program so that it can make superior human resources.Keywords: kampus merdeka, merdeka belajar, economy, strategic management, human resource